Integration and Hierarchy of Pork Markets in the EU: An Analysis from the Vantage of Graph Theory - Panos Fousekis; Vasilis Grigoriadis (German Journal of Agricultural Economics (GJAE), 2019)
The work investigates empirically the degree of integration and the hierarchical structure of the EU pork meat markets using tools and concepts from Graph Theory. The empirical results suggest: First, the strength of price co-movement has been closely related to the physical distance between national markets. This, has given rise to market clustering that largely corresponds to different
Keywords: 330